FAB LMB 96 Regimen for Newly Diagnosed Burkitt Lymphoma in Children: Single-center Experience. Issue 1 (January 2019) - Aydin, Burca; Akyuz, Canan; Kalkan, Neslihan; Kurucu, Nilgun; Varan, Ali; Yalcin, Bilgehan; Kutluk, Tezer
Abstract : Background/Objectives: The outcome of Burkitt lymphoma has improved by over 90%. In this study, demographic characteristics and outcomes of 57 patients with Burkitt lymphoma treated with FAB LMB 96 regimen are presented. Materials and Methods: Standard intensity arms were selected for all risk groups. Clinical characteristics, response to treatment, and outcome were evaluated. Results: The median age of 48 boys and 9 girls was 8.2 years. There were 2 (3%), 41 (72%), and 14 (25%) patients in the low, intermediate, and high-risk groups, respectively. Patients were followed-up for a median of 50 months. The 5-year overall survival and event-free survival rates for the study group were 90.8% and 87.4%, respectively. Two patients in the low-risk group are still alive without evidence of disease for 17 and 57 months. The 5-year overall survival rates were 95% and 78% for intermediate and high-risk patients, and the 5-year event-free survival rates were 93% and 62%, respectively. At the end of induction, 58% of patients had complete response, and 42% (n=24) had residual tumors. A total of 16 of 24 patient biopsies showed no viable tumors. Conclusions: Our results confirm the previously published survival results of FAB LMB 96. The regimen is an effective regimen for mature B-cell non-Hodgkin lymphoma without radiotherapy or surgery even in central nervous system–positive patients. The most important prognostic factor is the complete response after induction chemotherapy. However, residual tumor at the end of consolidation might not always be a sign for unresponsive tumor. Tumoral residue should be radiologically well evaluated and biopsied if possible for viability before intensifying treatment.